Perbandingan Pelarut Ekstrak Air, Etanol 70%, dan N-Heksana Herba Utasupe terhadap Kandungan Metabolit Sekunder Menggunakan Skrining Fitokimia - Alsen Diamel Oematan; Listyawati Nurina; Desi Indriarini; Anita L. Shinta Amat; Muhajirin Dean (Yayasan Jompa Research and Development, 2026)
Traditional medicine is a medicine that is used for generations from ancestors and inherited until now. The use of herbal medicinal products in the last three decades has increased rapidly. Indonesia is one of the countries that has a lot of biodiversity. Indonesia has millions of varieties of plants that can be used as herbal medicine. Utasupe is a plant that is one of the herbal medicines used by people from Ende Island, Ende Regency, East Nusa Tenggara Province as an herbal medicine for constipation conditions. Knowing the comparison of secondary metabolite compounds of water extract, 70% ethanol, and n-hexane Herba Utasupe from Ende Island District. Research used in true experimental design research with posttest only control group design research design. This study used phytochemical screening methods, to see changes in color/shape that indicate the presence and absence of secondary metabolite compounds present in water extracts, 70% ethanol, and n- hexane Utasupe herbaceous plants from Ende Island District. The sample in this study was Utasupe Herba plants that met the inclusion criteria and exclusion criteria. Data analysis using nonparametric statistical methods, namely the fisher test. In water and ethanol solvents 70% obtained groups of secondary metabolite compounds alkaloids, flavonoids, tannins, and saponins. While in n-hexane solvents obtained a class of secondary metabolite compounds of alkaloids, flavonoids, steroids, and tannins. In statistical analysis using the fisher test, p values were obtained: 0.200 – 0.100 (p > 0.005). The results of this fisher test show that there is no significant difference between the three solvents. There is no comparison between water solvent, 70% ethanol, and n- hexane based on the results of statistical analysis using the Fisher test.